A moral vision for the presidential election. Issue 3 (9th July 2020) - Stone, Ronald H.
Abstract: The essay celebrates the "Mirror of Princes" writing of political philosophy that appeared in Augustine's City of God, the history of Western political philosophy and in the political thought of ancient China. It upholds the tradition of the good ruler while noting the ambiguities of morality in politics. It notes the political power of the American president in the current global context. While emphasizing the need for the good ruler to love the people he serves it focuses on the need for reform in health care, education, and race relations.